Penggunaan Metode Problem Based Learning dalam Pembelajaran Keterampilan Menulis Teks Persuasif Kelas VIII MTsN 1 Tangerang Selatan - Sari, Niken Rahma (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to describe the use of the Problem Based Learning (PBL) method in learning to write persuasion texts for grade 8-5 MTsN 1 South Tangerang students. The method used in this study is descriptive qualitative method. Researchers used subjects, namely grade 8-5 MTsN 1 South Tangerang students with a total of 34 students, consisting of 14 male students and 20 female students. This study used data sources derived from the results of persuasive speech text writing exercises and was done in groups. Then for the main data analysis technique, research was carried out to calculate the results of the test of writing students' persuasive speech texts through frequency and percentage. The results of this study show that the Problem Based Learning method can be used as a learning model to improve students' ability to write persuasive speech texts so that students appear more active and enthusiastic when participating in learning.